Alcohol drinking patterns have a positive association with cognitive function among older people: a cross-sectional study - Akagi, Yuya; Kabayama, Mai; Gondo, Yasuyuki; Masui, Yukie; Yasumoto, Saori; Klinpudtan, Nonglak; Srithumsuk, Werayuth; Godai, Kayo; Ikebe, Kazunori; Akasaka, Hiroshi; Yokoyama, Serina; Nozato, Yoichi; et al. (BMC geriatrics, 2022)
Background The relationship between moderate alcohol drinking or other alcohol drinking patterns such as frequency, beverage type, and situation of drinking and cognitive function is not sufficiently clear in older people. The purpose of this study was to investigate the association between alcohol drinking patterns and cognitive function in community-dwelling Japanese people aged 75 and over. Methods This study was a cross-sectional design based on a prospective cohort study called the SONIC study. Subjects were older people aged 75-77 or 85-87 who voluntarily participated in 2016-2017. Drinking information was collected for daily drinking frequency, daily drinking intake, beverage type, and non-daily drinking opportunity. Cognitive function was measured using the Japanese version of the Montreal Cognitive Assessment (MoCA-J). Other potential confounding factors evaluated were age, sex, medical factors, and psychosocial factors. An analysis of covariance was performed to evaluate the MoCA-J score relative to drinking frequency or alcohol intake. Multiple regression analysis was performed to investigate the association between beverage type or non-daily drinking opportunity and the MoCA-J score. Results The final number of participants analyzed was 1,226. The MoCA-J score for participants who reported drinking alcohol 1–6 days/week was significantly higher than that for those who reported drinking none or every day. No significant difference in the MoCA-J score was observed relative to daily alcohol intake. In terms of beverage type, wine was associated positively with the MoCA-J score. Non-daily drinking opportunity was also associated positively with the MoCA-J score. Conclusions Moderate-frequency drinking, wine consumption, and non-daily drinking opportunities were associated with higher cognitive function in community-dwelling Japanese aged 75 and over. Further longitudinal studies are needed to clarify the causal relationships.